2011
DOI: 10.1002/cctc.201100115
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Active Sites in NiNbO Catalysts for the Direct Conversion of Ethane to Acetonitrile or Ethylene

Abstract: NiO nanoparticles that are highly active for the ethane activation have been prepared. These nanoparticles have been dispersed on the surface of two different Nb2O5 materials by using a novel dry nanodispersion method. This article describes the characterization and catalytic behavior of both series of catalysts as well as the nature of the active sites required for the transformation of ethane into acetonitrile and/or ethylene. It is demonstrated how such active sites present in the catalysts are obtained thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…13 In this mainly unexplored line, sepiolite seems very interesting as support for ZnO-based H 2 S sorbents. 26,27 The scope of this work is to obtain conformed solids with high surface area and porosity containing a good active phase for H 2 S sorption, ZnO, preserving the nanodispersion and the sulfidation capacity. 14 Sepiolite is a natural hydrated magnesium silicate fibrous clay with inter-and intra-particle porosity and chemical composition 19,20 Additionally, sepiolite may catalyze the Claus reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In this mainly unexplored line, sepiolite seems very interesting as support for ZnO-based H 2 S sorbents. 26,27 The scope of this work is to obtain conformed solids with high surface area and porosity containing a good active phase for H 2 S sorption, ZnO, preserving the nanodispersion and the sulfidation capacity. 14 Sepiolite is a natural hydrated magnesium silicate fibrous clay with inter-and intra-particle porosity and chemical composition 19,20 Additionally, sepiolite may catalyze the Claus reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the use of dry mixing procedures has been demonstrated as an efficient route to tailor the catalytic performance. 26,27 The scope of this work is to obtain conformed solids with high surface area and porosity containing a good active phase for H 2 S sorption, ZnO, preserving the nanodispersion and the suldation capacity. Nanostructured composite materials containing sepiolite and dispersed ZnO nanoparticles have been prepared by impregnation and dry mixing methods and conformed as monoliths by extrusion.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported a solvent‐free and residue‐free preparation method to prepare hierarchical nanoscaled catalysts dispersed on microscaled particles (support) 18. 19 Thus, mixing oxides of dissimilar materials by this nanodispersion method makes it possible to obtain hierarchical nanoparticles–microparticles systems with unusual properties. After the partial reaction of the two oxides, the interfaces created reveal new and interesting properties attributed to proximity and diffusion phenomena,20, 2 which is relevant at the nanoscale range.…”
Section: Introductionmentioning
confidence: 99%
“…After the partial reaction of the two oxides, the interfaces created reveal new and interesting properties attributed to proximity and diffusion phenomena,20, 2 which is relevant at the nanoscale range. Moreover, the support and supported nanoparticles interactions can be used to tune or create magnetic, piezoelectric, and catalytic properties, depending on the temperature treatment for the nanodispersed material 19. 22, 23 Because of the small particle sizes, it is possible to characterize changes in structure spectroscopically 24.…”
Section: Introductionmentioning
confidence: 99%
“…19 Since that study indicated that NiO catalyst was not able to incorporate the nitrile group into ethane molecule in absence of niobium in the catalyst formulation, we investigated supported NiO/Nb 2 O 5 catalysts for ethane ammoxidation. 27,28 Two different synthesis methods for those supported catalysts were studied, a conventional impregnation, 27 and a novel dry mixing method. 28 In both cases, these studies show that NiO oxide phase is required along with the presence of a mixed Ni-Nb-O phase to obtain efficient ethane ammoxidation.…”
Section: Introductionmentioning
confidence: 99%